Neuropeptide S activates paraventricular oxytocin neurons to induce anxiolysis - Grund, Thomas; Goyon, Stephanie; Li, Yuting; Eliava, Marina; Liu, Hai-Kun; Charlet, Alexandre; Grinevich, Valéry; Neumann, Inga D. (The journal of neuroscience, 2017)
Neuropeptides, such as neuropeptide S (NPS) and oxytocin (OXT), represent potential options for the treatment of anxiety disorders due to their potent anxiolytic profile. In this study, we aimed to reveal the mechanisms underlying the behavioral action of NPS, and present a chain of evidence that the effects of NPS within the hypothalamic paraventricular nucleus (PVN) are mediated via actions on local OXT neurons in male Wistar rats. First, retrograde studies identified NPS fibers originating in the brainstem locus coeruleus, and projecting to the PVN. FACS identified prominent NPS receptor expression in PVN-OXT neurons. Using genetically encoded calcium indicators, we further demonstrated that NPS reliably induces a transient increase in intracellular Ca2+ concentration in a subpopulation of OXT neurons, an effect mediated by NPS receptor. In addition, intracerebroventricular (i.c.v.) NPS evoked a significant somatodendritic release of OXT within the PVN as assessed by microdialysis in combination with a highly sensitive radioimmunoassay. Finally, we could show that the anxiolytic effect of NPS seen after i.c.v. or intra-PVN infusion requires responsive OXT neurons of the PVN and locally released OXT. Thus, pharmacological blockade of OXT receptors as well as chemogenetic silencing of OXT neurons within the PVN prevented the effect of synthetic NPS. In conclusion, our results indicate a significant role of the OXT system in mediating the effects of NPS on anxiety, and fill an important gap in our understanding of brain neuropeptide interactions in the context of regulation of emotional behavior within the hypothalamus. - SIGNIFICANCE STATEMENT Given the rising scientific interest in neuropeptide research in the context of emotional and stress-related behaviors, our findings demonstrate a novel intrahypothalamic mechanism involving paraventricular oxytocin neurons that express the neuropeptide S receptor. These neurons respond with transient Ca2+ increase and somatodendritic oxytocin release following neuropeptide S stimulation. Thereby, oxytocin neurons seem essential for neuropeptide S-induced anxiolysis, as this effect was blocked by pharmacological and chemogenetic inhibition of the oxytocin system.
Gesehen am 17.08.2021